The Hydrolyzed Mil-88B(Fe) With Improved Surface Area for High-Capacity Lithium Ion Battery - Guo, Mingxuan; Li, Haibo (Frontiers in Energy Research, 2021)
In this work, Mil-88B(Fe) is modified by a facile hydrolysis method for high-performance lithium ion battery (LIB). The hydrolyzed Mil-88B(Fe) [H-Mil-88B(Fe)] heritages the spindle-like shape of Mil-88B(Fe) and forms a porous structure, which possesses relatively high specific surface area (427.86 m2 g−1). It is 15 times higher than that of pristine Mil-88B(Fe). As anode for LIB, it reaches to high specific capacity of 600.1 mAh g−1 after 100 cycles at 100 mA g−1, while it is 312.5 mAh g−1 for pure Mil-88B(Fe). Furthermore, the kinetic analysis on i=avb reveals that the b value of H-Mil-88B(Fe) is 0.888, which suggests the mixed contribution from the diffusion and capacity reactions. Furthermore, the capacitance contribution fractions of H-Mil-88B(Fe) are 47.6%, 53.28%, 56.88%, 74.68%, and 69.14% at the sweep rate of 0.2, 0.4, 0.6, 0.8, 1.0 mV s−1, respectively, demonstrating a capacitance-dominated charge storage process at fast charging rates.